Safe harbour - Steel, Danielle (New York : Delacorte Press, 2003)
Struggling with a terrible accident that devastated her family, young Pip meets artist Matt Bowles, whose friendship helps Pip and her mother heal, until an unresolved issue from Matt's past compromises their progress.
Keywords: Mothers and daughters -- Fiction; Loss (Psychology) -- Fiction; Artists -- Fiction; Girls -- Fiction; San Francisco (Calif.) -- Fiction; Domestic fiction; Love stories